The construction of demand and professional interaction in educational actions at School Health Program (Research, Society and Development, 2020)
The government action is necessary through public health policies to integrate health and education. This study aimed to identify which aspects are taken into account for the construction of the demand of educational practices for the prevention of Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome HIV/AIDS carried out by School health program (PSE) with students from a public school, and how is the involvement of health and education professionals in this process. This is a qualitative descriptive-exploratory study where semi-structured interviews were conducted with six professionals of a Health Strategy Team family and observation of teaching practices with students were held. For the planning of educational practices the experience of community health worker in the community serves as support for actions in school, as well as the knowledge of the epidemiological situation of  HIV/AIDS in the city and the context of students. It was evident that the nurse has a supporting role in the actions that the team working on the PSE realizes the important participation of teachers, however, they point to the insecurity in teachers to address the issue HIV/AIDS. Knowledge of the issues presented, makes it possible to problematize them and be thoughtful alternative to overcome evidence as emerging from this research, since they can be vulnerable producers in the context of educational practices.